2012
DOI: 10.4081/jae.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment: an application to poplar for energy cultivated in Italy

Abstract: The development of the bioenergy sector has led to an increasing interest in energy crops. Short rotation coppices (SRC) are forestry management systems in which fast-growing tree species are produced under intensive cultivation practices to obtain high wood chips yields. In Italy, most SRC plantations consist of poplar biomass-clones. SRC plantations can be carried out with different management systems with diverse cutting times; consequently, the cultivation system can be crucial for attaining high yields de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
3
15
1
Order By: Relevance
“…The result of our study are in accordance with the literature (Bachmaier et al, 2013;Pöschl et al, 2010Pöschl et al, , 2012Wulfa et al, 2006;Bacenetti et al, 2012aBacenetti et al, , 2012bSchumacher et al, 2010;Meyer-Aurich et al, 2012), which shows that electricity production from biogas has huge potential for energy savings and a reduction of GHG emissions.…”
Section: Alternative Scenariosupporting
confidence: 95%
See 1 more Smart Citation
“…The result of our study are in accordance with the literature (Bachmaier et al, 2013;Pöschl et al, 2010Pöschl et al, , 2012Wulfa et al, 2006;Bacenetti et al, 2012aBacenetti et al, , 2012bSchumacher et al, 2010;Meyer-Aurich et al, 2012), which shows that electricity production from biogas has huge potential for energy savings and a reduction of GHG emissions.…”
Section: Alternative Scenariosupporting
confidence: 95%
“…Also, 1 kWh of electricity (kWh e ) produced in a CHP using biogas was the functional unit (FU) for the entire electricity production system. The selection of these FUs is in agreement with other biogas LCA studies (Dressler et al, 2012;Pöschl et al, 2012;Bacenetti et al, 2012aBacenetti et al, , 2012b.…”
Section: Functional Unitsupporting
confidence: 79%
“…A similar pattern has been reported in other LCA studies of willow cultivation [37,69]. Gasol et al [70] and Bacenetti et al [71] concluded that emissions connected to fertilisation cause the largest climate impact in a poplar cultivation system. The direct N 2 O soil emissions originate from the N fertiliser applied and from the N content in the residues.…”
Section: Discussionsupporting
confidence: 63%
“…The climate impact from cultivation of willow and poplar has also been investigated in several other studies (e.g. [16,70,71]). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive evaluation of SRC cultivation focusing on the GHG balance of such systems together with other environmental impacts, for example, NO 3 leaching losses, needs to have a long‐term perspective. Also, differences in management practices, in particular changing rotation cycle length, can have significant impacts on biomass yield and environmental effects such as soil C storage or soil N 2 O emissions (e.g., Fang et al ., ; Bacenetti et al ., ).…”
Section: Introductionmentioning
confidence: 97%